Analysis of Creativity Management in Achieving Maximum Human Resource Productivity - Djunarto; Nanda Ravenska; Teni Listiani; Herty Ramayanti Sinaga; Gusti Noorlitaria Achmad (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
Creativity management and human resource productivity are crucial pillars that determine the sustainability and competitiveness of an organization in this dynamic modern era. Balancing these two elements requires a holistic leadership approach, where decision-makers focus not only on the quantity of work output but also on the quality of innovative ideas generated. The purpose of this study is to analyze creativity management in achieving maximum human resource productivity. This research uses narrative research. This narrative is supported by secondary data sources, such as books and journals. The results of this study indicate that creativity management is no longer simply facilitating unique ideas, but rather a strategic approach to converting employees' cognitive potential into high-value output. In the context of achieving maximum human resource productivity, creativity acts as a catalyst for efficiency, problem-solving, and process innovation. To transform creativity into real productivity, management must manage three things are the work environment, flexible work design, and an appropriate reward system